2005
DOI: 10.2189/asqu.2005.50.3.440
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Genealogies and the Persistence of Gender Inequality: The Case of Silicon Valley Law Firms

Abstract: Using a study on foundings of Silicon Valley law firms, I propose and test an organizational theory on the genealogical persistence of gender inequality that emphasizes the routines (or blueprints) and experiences that founders transfer from their parent firms to their new firms. This transfer links the parent firm's gender hierarchy to women's advancement opportunities in the new firm. Founders from parent firms that historically had women in leadership positions, such that female leadership is institutionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 70 publications
6
131
0
3
Order By: Relevance
“…Early-career individuals are more susceptible to environmental influence (Marquis and Tilcsik 2013) and to learning new skills, work routines, and practices, and these influences persist through their careers. Early professional training influences individuals' norms and habits (Bercovitz and Feldman 2008) and their likelihood of adopting certain types of organizational practices; early social networks and socialization also influence subsequent career decisions (McEvily et al 2012;Phillips, 2005). External contexts also shape the learning managers develop on the job: managers tend to acquire a different set of skills if they learn their trade during a period of resource scarcity than if they do so when resources are abundant (Schoar and Zuo, 2011;Malmendier and Nagel, 2011) and the more similar the initial level of organizational munificence to subsequent periods, the higher managerial performance will be (Tilcsik, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Early-career individuals are more susceptible to environmental influence (Marquis and Tilcsik 2013) and to learning new skills, work routines, and practices, and these influences persist through their careers. Early professional training influences individuals' norms and habits (Bercovitz and Feldman 2008) and their likelihood of adopting certain types of organizational practices; early social networks and socialization also influence subsequent career decisions (McEvily et al 2012;Phillips, 2005). External contexts also shape the learning managers develop on the job: managers tend to acquire a different set of skills if they learn their trade during a period of resource scarcity than if they do so when resources are abundant (Schoar and Zuo, 2011;Malmendier and Nagel, 2011) and the more similar the initial level of organizational munificence to subsequent periods, the higher managerial performance will be (Tilcsik, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This is remarkable given that most entrepreneurs are born in existing organizations (Bhide, 1994;Sørensen and Fassiotto, 2011). Incumbent firms may indeed be arenas for learning about the entrepreneurial process (Gompers et al, 2005;Phillips, 2005;Elfenbein et al, 2010). A few studies have, yet, analyzed the influence of coworkers and confirmed that the nature of an individual's career experiences not only exerts a direct effect on her own knowledge and attitudes, but also "spills over" to colleagues, by influencing the informational and normative environment in which employees make entrepreneurial entry decisions (e.g., Nanda and Sørensen, 2010).…”
Section: Entrepreneurial Bosses Gender and Employees' Choices For Ementioning
confidence: 99%
“…The literature on new firm survival stresses that the founder or the founding team plays a significant role in the process of overcoming the liability of newness. The founder plays a key role in outlining the initial strategy by defining the organization's culture, implementing routines, and so on (see, e.g., Phillips (2005)). As we argue above, the organizational blueprint is indisputably key to high firm performance and is not easily altered, rendering the founder's initial imprint on the organization highly significant for long-term performance.…”
Section: Controlsmentioning
confidence: 99%
“…First, it is argued that entrepreneurs often build on organizational routines familiar to them, adapting the organizational features of their previous employer (Hannan and Freeman, 1986;Baron and Hannan, 2002;Phillips, 2005). This argument indicates that the parent firm plays a role in shaping the new organization.…”
Section: Controlsmentioning
confidence: 99%
See 1 more Smart Citation